Introduction to the Concept and Practice of Using Arrays in Programming Languages ​​at Senior High School 2 Gunung Talang, Solok Regency: Pengenalan Konsep dan Praktik Penggunaan Array pada Bahasa Pemrograman di SMA 2 Gunung Talang Kabupaten Solok - Rima Liana Gema; Mutiana Pratiwi; Ruri Hartika Zain; Rini Sovia (KPN Kopertis X, 2023)
Introduction to the Concept and Practice of Using Arrays in Programming Languages ​​is an effort to provide education and guidance to teachers at Senior High School 2 Gunung Talang, Solok who are interested in computer programming. Knowledge of the use of arrays in programming languages ​​is an important basis in the increasingly developing world of information technology. This community service activity aims to provide a broader understanding of the concepts and practices of using arrays in programming languages, especially for those who do not have a technical background in programming. In this activity, participants will be invited to understand the basic concepts of arrays, how to declare, initialize and access array elements in programming languages. This activity will provide an introduction to various types of arrays, such as one-dimensional arrays, two-dimensional arrays, and multidimensional arrays, as well as provide examples of practical use in everyday programming. Participants will also be taught about the benefits of using arrays, including how they can simplify code, increase efficiency, and optimize data management. It is hoped that the results of this service will provide benefits to the community by increasing their understanding of the use of arrays in programming languages. With this knowledge, participants become better prepared to overcome programming challenges and apply them in various fields, such as software development, data analysis, and information technology in general